Analyses of Precore and Core Promoter Mutations of Hepatitis B Virus in Patients with Chronic Hepatitis B in Surabaya, Indonesia - . JUNIASTUTI; EDUARDUS BIMO AKSONO; TAKAKO UTSUMI; YOSHIHIKO YANO; . SOETJIPTO; YOSHITAKE HAYASHI; HAK HOTTA; FEDIK ABDUL RANTAM; HERNOMO ONTOSENO KUSUMOBROTO; MARIA INGE LUSIDA (Indonesian Society for microbiology, 2010)
Mutations of precore (A1896) and core promoter (T1762/A1764) of hepatitis B virus can reduce HBeAg production. These mutations are frequently found in the late HBeAg seroconversion. However, it has been a controversy about the role played by precore and core promoter mutations in determining outcome of chronic hepatitis B. In the present study, the variability of precore and core promoter of hepatitis B virus were analyzed using PCR amplification and sequencing, according to the outcome (viral load and HBeAg/anti-HBe) in chronic hepatitis B patients in Surabaya. The study groups included 5 patients with uncomplicated chronic hepatitis B and 10 patients with chronic hepatitis B and liver cirrhosis in Dr. Soetomo Hospital, Surabaya. The control group included 6 blood donors obtained from Indonesia Red Cross, Surabaya. All groups were HBsAg positive. Precore mutation A1896 was predominant in all groups (60%-67% of each), together with precore variant T1858. As reported, precore variant T1858 is a prerequisite for precore A1896 and characteristic for viral genotype. Nevertheless, core promoter mutations T1762/A1764 were predominant only in LC patients (60%). All of these mutations were found mostly after HBeAg seroconversion (anti-HBe+). Of most samples with anti-HBe+, precore mutation was related with low viral load (<105 copies/mL), but core promoter mutations with high viral load (>105 copies/mL). Precore mutation A1896 was predominant in all groups, but core promoter mutations T1762/A1764 were only predominant in LC patients. The precore mutation alone is possible not critical to indicate a poor outcome, the core promoter mutations must be considered also.